Fixed partial prosthesis impression: conventional versus digital method - Kukulka, Elisa Camargo [UNESP]; Souza, Joyce Rodrigues De [UNESP]; Gomes, Michelle De Sá Dos Santos [UNESP]; Andreatta Filho, Osvaldo Daniel [UNESP]; Nishioka, Renato Sussumo [UNESP] (Faculdade São Leopoldo Mandic, 2024)
The systematic review of the literature aimed to compare the conventional and digital impression methods for making fixed partial dentures using the current literature and to verify the applicability of the methods in the clinical routine. A search was carried out in the PubMed database using the keywords: Denture, Partial, Fixed and Dental Impression Technique from 2017 to 2022, of studies published in full, in English and free of charge. 520 articles were obtained from PubMed, 501 of which were from 2017 to 2022. After reading the titles and abstracts, 12 articles were excluded. In the end, 6 articles were selected, and 6 articles were later added by cross-reference, totaling 12 articles. Both impressions are good methods to perform impressions in fixed partial dentures, each method having its applications, advantages and disadvantages, and it is up to the dental surgeon to select the impression method to be used, considering the time spent for the impression, the learning curve, the personal, practical and social background, in addition to the cost used to acquire materials, clinical hours and laboratory work in the short and long term.

A revisão sistemática da literatura teve como objetivo comparar os métodos de moldagem convencional e digital para confecção de próteses parciais fixas com a literatura atual e verificar a aplicabilidade dos métodos na rotina clínica. Foi realizada uma busca na base de dados PubMed utilizando as palavras-chave: Denture, Partial, Fixed e Dental Impression Technique de 2017 a 2022, de estudos publicados na íntegra, em inglês e gratuitamente. Foram obtidos 520 artigos do PubMed, sendo 501 de 2017 a 2022. Após a leitura dos títulos e resumos, 12 artigos foram excluídos. Ao final, foram selecionados 6 artigos, sendo posteriormente adicionados 6 artigos por referência cruzada, totalizando 12 artigos. Ambas as moldagens são bons métodos para realizar moldagens em próteses parciais fixas, cada método tendo suas aplicações, vantagens e desvantagens, cabendo ao cirurgião-dentista selecionar o método de moldagem a ser utilizado, considerando o tempo gasto para a moldagem, a curva de aprendizado, o background pessoal, prático e social, além do custo de aquisição de materiais, horas clínicas e trabalhos laboratoriais a curto e longo prazo.
Moldagem em prótese parcial fixa: método convencional versus digital
Keywords: Dental impression technique; Dentistry; Fixed partial denture; Técnica de moldagem odontológica; Odontologia; Prótese parcial fixa